Pelophylax ridibundus complex as bioindicator of the level of anthropogenic pollution of the environment - Bazarbayeva, Zhannat; Ilderbayev, Oralbek; Suleimenova , Ainash; Nurmukhambetova, Gaziza; Olzhayeva, Rauza; Dukenbayeva, Asiya; Issina, Ayzhan (Ecological Questions, 2025)
The work presents the relationship between the degree of pollution of water bodies and changes in the structure of internal organs of the marsh frogs, Pelophylax ridibundus complex, inhabiting these bodies of water. To determine this relationship, two natural lakes and one artificial water reservoir located in an industrialised area near the city of Astana in Kazakhstan were investigated and conclusions were drawn regarding the gradient of anthropogenic pollution. In addition, histological examinations of the gastrointestinal tract of frogs caught from these water bodies differing significantly in the gradient of heavy metal concentration were carried out. It was found that of the analyzed organs, the stomach and liver were the most sensitive to pollution. The concordance of the intensity of damage to these organs with the degree of pollution of the lakes and the reservoir, as determined by physicochemical analysis of the water, indicate that the studied species can be considered a bioindicator of early pollution of aquatic biotopes.